The Determinants of Fuji Apple Sales on E-Commerce Platforms in Indonesia (Insights from Multiple Linear Regression Analysis) - Herdiana Anggrasari; Rosita Dewati; Ayu Kumala Sari (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
E-commerce sites like Shopee, Tokopedia, and Bukalapak have multiplied in Indonesia, and this has completely changed how vendors offer their goods, especially agricultural goods like apples. These platforms provide a convenient and efficient means of reaching a broader consumer base, enabling sellers to compete in a dynamic digital marketplace. This study aims to analyze the key factors influencing Apple sales on e-commerce platforms, focusing on eight variables: price (X1), rating (X2), reviews (X3), reviews with pictures/videos (X4), seller type (X5), membership duration (X6), cashback promos (X7), and free shipping promos (X8). To achieve this goal, the researchers collected secondary data from the three platforms and employed a random sampling technique to select 40 apple sellers. Multiple linear regression analysis evaluated the relationship between these variables and total sales. The findings indicate that price, the number of reviews, and membership duration are significant predictors of Apple sales. Sellers who offer competitive pricing and accumulate positive reviews are more likely to attract buyers, while longer membership duration enhances credibility and trust among consumers. This study provides actionable insights for sellers aiming to optimize their sales strategies. By focusing on pricing, encouraging customer reviews, and building a trustworthy online presence, sellers can better navigate the competitive e-commerce environment. Additionally, these findings are valuable for e-commerce platform managers to refine their promotional tools and support mechanisms. The study illuminates agricultural e-commerce dynamics and shows how digital platforms can improve Apple's market accessibility and sales.